Coal structure in the oxidation - S, Munkhtsetseg; B, Munkh-Orchlon (Scientific transaction of the National University of Mongolia. Physics, 2022)
In the current paper we present the experimental results of Nuurstkhotgor coals in the original (as received) and with low temperature treatment and compared those experimental with the theoretical ones for the observing coal molecule structure specifics in the oxidation. Three groups of the paramagnetic centres are responsible for one narrow Lorentz 1 (0.18 mT), three broad Gaussian 1 and 2 (0.30-0.62 mT), three broadest Gaussian 3 and 4 (0.85-1.05 mT) lines found in the EPR spectrums in the two coal samples. An infrared spectrum obtained experimentally from the heated coal has established several differences from the spectra of the original coal by its number of the bands and the intensities. Main differences are located in the 3000 and 1000 cm-1 absorption region where the vibrations from the O-H and C-O bonding.